Emotions, heart rate and performance in archery. A case study - Robazza, C.; Bortoli, L.; Nougier, V. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: A case study of an elite female archer was conducted to gain insight into individual psychophysical reactions accompanying an athletic event, and to test predictions of pre-performance emotions effects upon performance. Good performance was expected when the actual pre-performance emotions resembled the recalled optimal emotion pattern. Conversely, poor performance was expected when the actual pre-performance emotions paralleled the recalled ineffective emotion pattern. METHODS: Experimental design: the investigation comprised individual emotion profiling, emotions and heart rate monitoring, final interview and performance evaluation. SETTING: The research was accomplished during the 1996 European Archery Championships, one of the most important international archery competitions. PARTICIPANT: An 18-year-old female athlete of the Italian archery national team. INTERVENTIONS: Because of the exploratory nature of the study, no intervention was implemented. MEASURES: Emotion profiling was carried out using an idiographic approach based on recalled optimal and poor performances, according to the Individual Zones of Optimal Functioning (IZOF) model. Emotions, heart rate, and performance were monitored across the five days of practice and competition. RESULTS: Individual pre-performance optimal emotion pattern, heart rate deceleration during shooting, consistent shooting scores were revealed throughout practice and competition. CONCLUSIONS: The good performance predicted on the basis of pre-performance emotion assessments was met and was confirmed by the archer's interpretation.